Stabilization through integration: the European rescue of Italian capitalism. Issue 4 (4th July 2019) - Petrini, Francesco
ABSTRACT: Since its origins European integration has been closely connected to the social tensions that capitalism generates. During the interwar years, one of the main rationales behind the push to deeper European economic integration was the search for increased prosperity as a means to prevent class conflict. After the economic collapse of the 1930s and the Second World War, the European Communities were an essential part of a larger effort towards the restoration of capitalism's legitimacy and hierarchies. Since the end of the 1970s, following the crisis of the post-Second World War regime, the stabilizing role of European integration assumed new modes. Italy, as a weak link in the chain of capitalist development, showed in advance and with the utmost clarity how this new role worked. In two crucial passages of the post-1945 country's history, when workers' unrest strongly challenged the existing capitalist hierarchies, European governance played a crucial role in their restoration. Both in the early 1960s and in the late 1970s the European ' vincolo esterno ' (external constraint) decisively helped the affirmation of the domestic deflationary forces.